MOHAMMAD SJAFE’I: PERAN INTELEKTUALITASNYA DALAM MENGEMBANGKAN PENDIDIKAN DI SUMATERA BARAT MELALUI RUANG PENDIDIK INS KAYUTANAM - Kiki Rizki Fauzi (Prodi Ilmu Sejarah, Jurusan Sejarah, Seni dan Arkeologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, bekerja sama dengan Masyarakat Sejarawan Indonesia, Jambi, 2022)
This article aim to analyze the intellectual role of Mohammad Sjafe'i in establishing the INS Kayutanam and the conception of educational thoght that he carries. The method based on heuristic, source criticism, interpretation, and historiography stages. From the research conducted it can be seen that the concept of education promoted by Mohammad Sjafe'i was the antithesis of colonial education which was currently underway. Therefore, Sjafe'i formulated a conception of education that promotes a balance between work, thoughts and feelings. The concept is then poured into three area of education, namely the hand, the brain, and the heart. His educational thought cannot be separated from his educational and cultural background. This conception was finally immortalized in a school which became known as INS Kayutanam. Mohammad Sjafe'i founded INS Kayutanam on October 31, 1926, exactcly one year after his return from studying in the Netherlands.